2008
DOI: 10.1080/00015458.2008.11680279
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Homologous Packed Red Blood Cell Transfusion on Patients’ Survival after Radical Surgical Treatment of Colorectal Cancer

Abstract: The aim of this study was to assess the impact of homologous packed red blood cell transfusion on patients' survival after radical surgical treatment of colorectal cancer. We analyzed a group of 257 colorectal cancer patients who had undergone radical operations (R0 resection) and who had been followed-up for at least 30 months. Overall survival (OS), disease specific survival (DSS), disease free survival (DFS), free of local recurrence survival (FLR) and free of metastases survival (FM) were recorded. 122 (47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Data on OS were from 24 articles [14, 8, 9, 11, 13, 14, 16, 17, 19, 21, 22, 24, 2830, 3236, 38]. The random-effects model showed that transfusion could decrease OS significantly (HR, 0.33; 95% CI, 0.24 to 0.41; I 2 = 61.9%; P < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on OS were from 24 articles [14, 8, 9, 11, 13, 14, 16, 17, 19, 21, 22, 24, 2830, 3236, 38]. The random-effects model showed that transfusion could decrease OS significantly (HR, 0.33; 95% CI, 0.24 to 0.41; I 2 = 61.9%; P < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles reported the trigger of transfusion. The comparison between transfusion and non-transfusion on OS was from five of these articles [8, 13, 14, 17, 32]; in the five articles, one [14] used intraoperative bleeding > 1000 ml as a trigger of transfusion, and the other four articles were included in the following meta-analysis. The triggers were Hb ≤ 6 g/dl and Hb ≤ 7–10 g/dl, and the results showed that transfusion could reduce OS compared with non-transfusion if the trigger level was either Hb ≤ 6 g/dl ( I 2 = 0%, HR = 0.28, 95% CI 0.14–0.43, P < 0.0001) or Hb ≤ 7–10 g/dl ( I 2 = 0%, HR = 0.63, 95% CI 0.35–0.90, P < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26,29,54,55 This included 2327 patients, and the length of stay was significantly longer in transfused compared to nontransfused patients (17.8 ± 4.8 vs 13.9 ± 4.7 days, P = 0.005). Table 3 shows the result of the stratified IRR meta-analysis for all-cause mortality.…”
Section: Length Of Hospital Staymentioning
confidence: 98%
“…Seventeen studies7,[29][30][31][35][36][37][38]44,[47][48][49][55][56][57][58][59] reported the number of cancer-related deaths in transfused (31.0%, 1252 cancer-related deaths in 4045 patients) and nontransfused patients (24.4%, 638 deaths in 2614 patients), corresponding to a pooled OR of 1.71 (95%CI 1.43 -2.05). Corresponding incidence rates in 23,098 patient years (transfused) and 16,093 patient years (nontransfused) were 5.4 and 4.0% per year, respectively, leading to an IRR of 1.45 (1.26 -1.66, P < 0.001).…”
mentioning
confidence: 98%
“…Since its first description in 1982 by Burrows and Tartter, 2 several investiga-tions reported decreased overall survival, [3][4][5][6] increased rates of tumor recurrence, 7 and higher morbidity [8][9][10] in patients receiving perioperative blood transfusions after colorectal cancer resection. 14,15 However, several studies did not demonstrate an association between blood transfusion and survival, [16][17][18][19][20][21][22][23][24] and even the analysis of 12,127 patients in a large recent meta-analysis failed to answer the question whether the observed association between blood transfusion and increased cancer recurrence is of causal or coincidental nature. [11][12][13] Consequently, the threshold for giving perioperative blood transfusions has increasingly risen over the past decade.…”
mentioning
confidence: 99%